Response of almond (Prunus dulcis) to different drip irrigation levels vis-à-vis various phenological stages on flowering and yield of almond cv. Shalimar - Khan, Ishtiyaq A; Swani, M; Mir, M A; Ahmad, N; Mushtaq, K; Hassan, G I (The Indian Journal of Agricultural Sciences, 2012)
Experiment was conducted to assess the effect of different irrigation levels vis-à-vis various stages of flowering, fruit set and yield of almond (Prunus dulcis Mill.) plantation cv. Shalimar. The results revealed that irrigation applied at various stages of growth and development improved flowering, fruit set and yield of almond significantly. Maximum bloom intensity, fruit set and yield were recorded with highest evaporation replenishment of 100 ETc applied throughout the season during first and second year respectively. The study further confirmed that highest flowering and yield attributes of almond recorded at 100% ETc level of irrigation were found to be statistically at par with measured parameters recorded at 75% ETc level of irrigation when applied at fruit growth stage and throughout the growth stage. The results revealed clearly that flowering and early fruit growth stages are the most critical stages of irrigation in almond and that post-harvest irrigation may prove to be beneficial.